The Implementation and Transformation of Kulintang Melodies in the Rite of Mak Kamalun: A Minimalist Composition Analysis - Kadafi, Fadel; HR, Hafif; Anggara, Rama (Institut Seni Indonesia Padangpanjang, 2025)
The fusion of traditional Indonesian musical material with modern Western aesthetics has become a field of exploration in musical composition. Kulintang, as a musical system from the Mamasa people (West Toraja/West Sulawesi) and the Maranao people of the Philippines, provides a rich source of melodic and rhythmic structures that have not been widely explored within a minimalist musical framework. This article aims to analyze the implementation and transformation of kulintang melodies in the orchestral composition